Pengaruh Gaya Kepemimpinan Terhadap Kapabilitas Inovasi Guru dalam Perspektif Organizational Learning - Miyv Fayzhall; Agus Purwanto; Masduki Asbari; Sucipto Basuki; Mustofa Mustofa; Dhaniel Hutagalung; Siti Maesaroh; Winanti Winanti; Gusli Chidir; Fransisca Sestri Goestjahjanti; Yulia Andriyani (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aims to measure the influence of transformational and transactional leadershipon the teacher innovation capability in one of private school in Tangearng mediated by organizational learning. Data collection was carried out by simple random sampling via electronic to a population of the teachers. The returned and valid questionnaire results were 199 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are transformational leadership have positive and significant effect on teacher innovation capability, both directly and through mediating organizational learning. While tansactional leadership has positive and significant effect on teacher innovation capability only through mediating organizational learning. Because, transactional leadership has not significant effect on the teacher innovation capability directly. This novel research is proposing a model to build innovation capability amongteachers through transformational and transactional leadeship with organizational learning as mediation. This research can pave the way to improve teacher readiness in facing the education4.0 era